Scientific landscape of organic waste management in Asian countries (1999-2025): A comprehensive bibliometric analysis - Fujianti, Lia Nurbanillah; Munawir, Munawir; Rachman, Indriyani; Matsumoto, Toru (Edelweiss Applied Science and Technology, 2026)
Organic waste management is a significant challenge for Asian countries. Research on this issue has grown rapidly; however, a comprehensive study mapping the development of research on organic waste in this region has not been conducted. This bibliometric analysis examines research trends in Asian countries from 1999 to 2025. The analysis provides insights into international publication distribution, author and institutional output, collaboration patterns, citation metrics, and research topic development over the studied period. The findings indicate that India, China, and Indonesia are the primary contributors, supported by productive institutions such as Universitas Indonesia. Many scientific studies are published in Scopus Quartile 1 journals. Notable authors in this field include Lee, Dutt, Singh, and Tiwari. The use of Black Soldier Fly for bioconversion and microbial processes is extensively cited. The scientific community frequently researches composting, anaerobic digestion, and vermicomposting. Currently, research emphasizes an integrated approach rather than conventional methodologies. These findings establish a solid foundation for future investigations, enhance regional scientific capabilities, and facilitate the development of better organic waste management solutions for Asian countries.